Isolation of linalool compounds of nampu rhizome essential oil (Homalomena occulta) by vacuum fractionation distillation method - Rusyda, Hasna; Sukardi, Sukardi; Diyah Dewanti, Beauty Suestining (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The perfume industry in various countries is increasingly expanding and the appeal of perfume comes from its distinctive scent. One of Indonesia's potential needs in the organic perfume industry is essential oils. Nampu rhizome (Homalomena occulta) has great potential and is widely spread on the island of Java. This is because the Nampu rhizome has the main chemical component in the form of linalool compounds, which are essential oil components with high economic value, so it needs to improve quality by increasing its purity. A technology that was developed to improve the purity of essential oils was vacuum fractionation distillation. The purpose of the study was to analyze the effect of temperature on the quality of distillation in the fractionation results of Nampu rhizome essential oil (linalool compound). The experiment used a material temperature factor between 135-160°C and > 160°C.The analysis of fractionation results was carried out on physical properties including refractive index, specific gravity, optical rotation, colour, and linalool compound with GC-FID and yield. The results showed a refractive index value of 1.4620 nD, specific gravity of 0.8647, optical rotation of -19.80, clear oil colour and yield of 69.80%. Chemical analysis with GC-FID improves the purity level of the final product against the linalool fraction increased by 10.02% or linalool purity by 90.92%.